2008
DOI: 10.1530/eje-07-0907
|View full text |Cite
|
Sign up to set email alerts
|

A variant of the IGF-I gene is associated with blood pressure but not with left heart dimensions at the age of 2 years: the Generation R Study

Abstract: Background and objective: A common variant of the IGF-I gene has been shown to be associated with cardiovascular disease in adulthood. The objective of this study was to examine whether this variant of the IGF-I gene is associated with blood pressure and left heart dimensions in early childhood. Research design and methods: This study was embedded in the Generation R Study, a population-based prospective cohort study from foetal life onwards. IGF-I promoter region was genotyped in DNA obtained from cord blood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Dual X Energy Absorptiometry (DXA) scanning and Fractional exhaled Nitric Oxide (FeNO) measurements have been performed in a smaller subgroup [60, 61]. Blood pressure was measured at the age of 24 months [62, 63]. Observations of parent–child interaction and behaviour, such as executive function, heart rate variability, infant-parent attachment, moral development, and compliance with mother and child have been repeatedly performed and with father and child once [6468].…”
Section: Measurementsmentioning
confidence: 99%
“…Dual X Energy Absorptiometry (DXA) scanning and Fractional exhaled Nitric Oxide (FeNO) measurements have been performed in a smaller subgroup [60, 61]. Blood pressure was measured at the age of 24 months [62, 63]. Observations of parent–child interaction and behaviour, such as executive function, heart rate variability, infant-parent attachment, moral development, and compliance with mother and child have been repeatedly performed and with father and child once [6468].…”
Section: Measurementsmentioning
confidence: 99%
“…Also, strategies for genetic scoring analyses are being developed to estimate predictive values of identified genetic variants [171,172]. Although a GWAS is available in children, we use DNA from both children and parents for genotyping for candidate gene or replication studies [173][174][175][176][177][178][179][180][181][182]. Missing data in DNA samples in children will be collected by blood sampling or other methods at follow-up measurements.…”
Section: Biological Samplesmentioning
confidence: 99%
“…These data are updates for a newborn infant group because previously published normative values collected in a small pediatric sample were acquired for subjects of different ages (0-18 years). 14,15 In other studies data obtained by Vogel et al 16 in a small study showed a higher LVM/m 2 in newborns, however Kozak-Barany et al found a lower LVM/BSA in a small group of healthy newborns. 17 This discrepancy could result from different techniques of assessing left ventricular parameters and the differences between populations.…”
Section: Map ≥75 Percentilementioning
confidence: 88%